Exposure to activity based anorexia impairs contextual learning in weight-restored rats without affecting spatial learning, taste, anxiety, or dietary-fat preference - Boersma, Gretha J. (Int J Eat Disord, 2015)
Relapse rates are high amongst cases of Anorexia Nervosa (AN) suggesting that some alterations induced by AN may remain after weight restoration. OBJECTIVE: To study the consequences of AN without confounds of environmental variability, a rodent model of activity based anorexia (ABA) can be employed. We hypothesized that exposure to ABA during adolescence may have long-term consequences in taste function, cognition, and anxiety-like behavior after weight restoration. METHODS: To test this hypothesis we exposed adolescent female rats to ABA (1.5 hrs food access, combined with voluntary running wheel access) and compared their behavior to that of control rats after weight restoration was achieved. The rats were tested for learning /memory, anxiety, food preference and taste in a set of behavioral tests performed during the light period. RESULTS: Our data show that ABA exposure leads to reduced performance during the novel object recognition task, a test for contextual learning, without altering performance in the novel place recognition task or the Barnes maze, both tasks that test spatial learning. Furthermore, we do not observe alterations in unconditioned lick responses to sucrose nor quinine (described by humans as “sweet” and “bitter” respectively). Nor did we find alterations in anxiety-like behavior during an elevated plus maze or an open field test. Finally, preference for a diet high in fat was not altered. DISCUSSION: Overall our data suggest that ABA exposure during adolescence impairs contextual learning in adulthood without altering spatial leaning, taste, anxiety, or fat preference.